2013
DOI: 10.1111/ropr.12035
|View full text |Cite
|
Sign up to set email alerts
|

Hungry for Information: Public Attitudes Toward Food Nanotechnology and Labeling

Abstract: What people think about food nanotechnology (nanofood) is under‐explored in the United States, especially outside of quantitative surveys. As such, we set out to examine public attitudes toward food nanotechnology in conversational, focus group settings in order to identify policy options for nanofood governance, and in particular, options for labeling. Through analysis of focus groups in six U.S. locations, we found that the vast majority of the participants wanted nanotechnology labels for all types of food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
2
51
0
Order By: Relevance
“…This relationship was also similar for consumers' attitudes about GM and nano-foods-more negative attitudes about GM and nano-food correlate to an increased desire for labeling. This is further supported by previous valuesbased findings that a majority of consumers support labeling of GM and nano-food technologies while maintaining a reluctance to consume GM foods (Brown and Kuzma 2013;Frewer et al 2013). In this sense, it is important to note that for some consumers, labels of this type likely represent a heuristic warning cue about the product rather than serve as a locus for information conveyance about the product.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This relationship was also similar for consumers' attitudes about GM and nano-foods-more negative attitudes about GM and nano-food correlate to an increased desire for labeling. This is further supported by previous valuesbased findings that a majority of consumers support labeling of GM and nano-food technologies while maintaining a reluctance to consume GM foods (Brown and Kuzma 2013;Frewer et al 2013). In this sense, it is important to note that for some consumers, labels of this type likely represent a heuristic warning cue about the product rather than serve as a locus for information conveyance about the product.…”
Section: Discussionsupporting
confidence: 57%
“…A recent focus group study from the US on nanofood reports findings that consumers desire nano-food labeling, but are not strictly opposed to all forms of nano-food technologies (Brown and Kuzma 2013). They found that consumers preferred nanomaterials when used in food packaging over use of nanomaterials as food ingredients and when used for improving food safety and nutritional content over other types of benefit.…”
Section: Introductionmentioning
confidence: 99%
“…[12] found that the use of nanotechnology in food and food packaging raises concerns of the consumers. [9] argue that people are not sure about the risks and benefits posed by J.eng.process.meng. 9 (1) 10-14 (2017) https://doi.org/10.7251/JEPM1709010K…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of previous studies [9]; [10]; [11]; [12]; [13] we developed a questionnaire to measure beliefs and attitudes towards nanotechnology and its use in food production. The questionnaire consisted of closed-ended questions (items) in which participants responded on a five-point grading scale (frequency, level of acceptability, level of agreement).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation